2020
DOI: 10.1186/s12875-020-01208-8
|View full text |Cite
|
Sign up to set email alerts
|

A pay for performance scheme in primary care: Meta-synthesis of qualitative studies on the provider experiences of the quality and outcomes framework in the UK

Abstract: Background The Quality and Outcomes Framework (QOF) is an incentive scheme for general practice, which was introduced across the UK in 2004. The Quality and Outcomes Framework is one of the biggest pay for performance (P4P) scheme in the world, worth £691 million in 2016/17. We now know that P4P is good at driving some kinds of improvement but not others. In some areas, it also generated moral controversy, which in turn created conflicts of interest for providers. We aimed to undertake a meta-synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
(289 reference statements)
0
24
0
2
Order By: Relevance
“…Regarding the influence of linking income with performance on the feelings of health workers, theoretical analysis based on self-determinant theory explains that too much financial incentives could destroy intrinsic motivation and reduce the enjoyment of health workers of tasks in the long term [31,32]. Some qualitative studies found that pay-for-performance directly using financial incentive to guide the behavior of health workers was detrimental to the autonomy and professionalism of health professionals [14,15]. Though bonding income with performance could push health workers to work harder on the incentivized targets, as earning more income is a driver of health workers to make more efforts, the fatigue of efforts and pressure also decrease the utility of health workers at the same time [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the influence of linking income with performance on the feelings of health workers, theoretical analysis based on self-determinant theory explains that too much financial incentives could destroy intrinsic motivation and reduce the enjoyment of health workers of tasks in the long term [31,32]. Some qualitative studies found that pay-for-performance directly using financial incentive to guide the behavior of health workers was detrimental to the autonomy and professionalism of health professionals [14,15]. Though bonding income with performance could push health workers to work harder on the incentivized targets, as earning more income is a driver of health workers to make more efforts, the fatigue of efforts and pressure also decrease the utility of health workers at the same time [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, how the health workers perceive and feel the PBP has been seldom studied. Some qualitative studies [14,15] found the negative consequences of PBP on feelings of health workers because PBP using financial incentives to change the medical professional behaviors is against medical professionalism and clinical autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analysis based on self-determinant theory explains that too much nancial incentives would destroy the intrinsic motivation, and reduce the the enjoy of health workers on the tasks in the long term [20,21]. Some qualitative studies found that pay-for-performance directly using nancial incentive to guide the behavior directions of health workers were detrimental to autonomy and professionalism of health professionals [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…These actions ensure it becomes a shared philosophy of care and action designed to improve the likelihood of benefits. Thus, the JBDS ‐ IP frailty guidance, 1 which is supported by recent national and international clinical guidance on managing frailty, 18,19 should be implemented in parallel with initiatives in primary care such as the introduction of six indicators relating to frailty within the Quality Outcomes Framework contract in the United Kingdom 20 …”
mentioning
confidence: 99%
“…Thus, the JBDS-IP frailty guidance, 1 which is supported by recent national and international clinical guidance on managing frailty, 18,19 should be implemented in parallel with initiatives in primary care such as the introduction of six indicators relating to frailty within the Quality Outcomes Framework contract in the United Kingdom. 20 No one can deny the immense success of the United Kingdom-based National Diabetes Audit (NaDia) in enhancing the quality of diabetes inpatient care (such as reduced rates of medication errors, severe hypoglycaemia and inpatient occurrence of foot ulcers) 21 and the recent Getting it Right First Time initiative (GIRFT) which aims to improve diabetes care and services for all in the United Kingdom by making key recommendations in six areas including type 1 diabetes, procurement and medicines optimisation, and diabetic footcare. 22 We urge both of these initiatives and similar projects elsewhere to consider proactively to introduce frailty measures (since the presence of frailty will influence selfcare and foot care ability, hypoglycaemia incidence, insulin usage and error rates, etc) in the future work.…”
mentioning
confidence: 99%